Lightning danger indexing in the changing climate - Iwański, Rafał; Wypych, Agnieszka (Quaestiones Geographicae, 2025)
This research is focused on the danger that Cloud-to-Ground (CG) lightning stroke events pose in Poland in the face of the changing climate. The data utilised come from the lightning detection and localisation network PERUN run by the Institute of Meteorology and Water Management – National Research Institute (IMWM-NRI) in Poland from 2002 to 2023. To present the lightning stroke spatial variability, the raw data were converted and 0.2 × 0.2 grid was used to standardise the output. It can be concluded that in the time span of 22 years, the system recorded 29,936,514 lightning strokes that were used to calculate lightning stroke densities, intensities, centroids, trends and to create a novel index estimating the danger the lightning poses to human life and industry. The monthly variation presents extended thunderstorm season starting from April to September, with July as the peak month. Both the lightning stroke number and intensity (power) are in the rising trend in Poland, especially in the pre-seasonal and post-seasonal months. The highest value of the proposed Lightning Danger Index (LDI) is calculated in the central (peak LDI value of 0.968) and SE parts of Poland during the thunderstorm high season in June, July and August with the mean value of 0.652 for the whole period of the study.